Engineered exosomes restore miR-508-5p expression in uterine corpus endometrial carcinoma and reduce tumor progression and metastasis by targeting DLL3 - Li, Yue-Ying; Liu, Hui; Feng, Jia-Lu; Tian, Wen-Yan; Du, Juan; Zhang, Li-Ping (Frontiers in Oncology, 2025)
IntroductionEndometrial cancer (EC) is a growing global health concern. Understanding the molecular mechanisms driving EC is crucial for developing effective diagnostic and therapeutic strategies. This study investigates the roles of DLL3 and miR-508-5p in EC progression and explores a therapeutic approach using engineered exosomes to modulate their expression.MethodsTCGA data were analyzed, in vitro and in vivo experiments were performed to assess DLL3 and miR-508-5p function, and bioinformatics was used to confirm their interaction. Mesenchymal stem cells (MSCs) were engineered to produce miR-508-5p-overexpressing exosomes, and their therapeutic effects were tested in mouse models.ResultsElevated DLL3 and downregulated miR-508-5p were observed in EC and correlated with poor outcomes. miR-508-5p directly targets DLL3. Engineered exosomes restored miR-508-5p, inhibited DLL3, and reduced tumor growth and metastasis in mouse models.DiscussionThe findings highlight the roles of DLL3 and miR-508-5p in EC. Targeting the miR-508-5p/DLL3 axis via exosome-mediated delivery represents a promising therapeutic strategy for EC.